Maintenance of CD8+ memory T lymphocytes in the spleen but not in the bone marrow is dependent on proliferation. Issue 11 (11th October 2017) - Siracusa, Francesco; Alp, Özen Sercan; Maschmeyer, Patrick; McGrath, Mairi; Mashreghi, Mir‐Farzin; Hojyo, Shintaro; Chang, Hyun‐Dong; Tokoyoda, Koji; Radbruch, Andreas
Abstract: It is current belief that numbers of CD8 + memory T lymphocytes in the memory phase of an immune response are maintained by homeostatic proliferation. Here, we compare the proliferation of CD8 + memory T lymphocytes, generated by natural infections and by intentional immunization, in spleen and bone marrow (BM). Fifty percent of CD8 + memory T lymphocytes in the spleen are eliminated by cyclophosphamide within 14 days, indicating that numbers of at least 50% of splenic CD8 + memory T lymphocytes are maintained by proliferation. The numbers of CD8 + memory T lymphocytes in the BM, however, were not affected by cyclophosphamide. This stability was independent of circulating CD8 + memory T cells, blocked by FTY720, showing that BM is a privileged site for the maintenance of memory T lymphocytes, as resident cells, resting in terms of proliferation. Abstract : Cyclophosphamide does not eliminate CD8 + memory T cells of the bone marrow, demonstrating that they do not proliferate, and their numbers are maintained in the presence of FTY720, demonstrating that they are resident.